A participatory multicriteria decision analysis of the adaptive capacity-building needs of Jordan's agribusiness actors discloses the indirect needs downstream the value chain as “post-requisites” to the direct upstream needs - Abdel-Fattah, Ahmad; Al Hiary, Masnat (Frontiers in Sustainable Food Systems, 2023)
Climate adaptive capacity-building initiatives and activities in the developing countries, particularly those implemented by development agencies and international organizations, commonly focus on upstream direct adaptive capacity-building needs of targeted vulnerable sectors. However, overlooking building a holistic climate-adaptive capacity of a vulnerable sector down to the last link of its value chain renders inadequate contribution, jeopardizes the adaptation intervention, and prevents achieving high level of buy-in of the chain actors for the results of the sought capacity-building programs. Thus, this study developed a hybridization of system-wide and participatory (focus groups-based) multi-criteria decision analysis (MCDA) to conduct adaptive-capacity needs assessment for the actors of the agribusiness value chain of the developing country of Jordan. Our holistic approach enabled highlighting the sector’s climate vulnerability along the value chain, conducting self-regulated adaptive Training Needs Assessment (TNA) of the sector’s actors, and identifying and prioritizing their real adaptive capacity-building needs. This approach proved to be uniquely advantageous in comparison to the sector’s commonly used questionnaire-based surveys that are limited-participatory, researcher-regulated, and subsystems-oriented approaches. The advantages of this hybrid hands-on and wide-ranging MCDA-TNA approach is evident in its revelation of unique results. The approach enabled actors of such highly vulnerable sector to spontaneously identify and prioritize the indirect downstream climate adaptive capacity-building needs surprisingly over the direct needs. This is due to the fact that the actors considered the indirect needs more important to their businesses and livelihoods than the direct needs, thus considering the indirect needs as “post-requisites”, i.e., post-condition, to the fate of the direct upstream needs. The hybrid approach also enabled the beneficiaries to themselves formulate the intervention’s outcomes, unveil factors ignored by conventional researcher-controlled approaches, secure high buy-in of the self-attained results, and prioritize actual adaptive capacity-building demands. This robust combination of qualitative research methods and tools could be straightforwardly applied to design and conduct efficient and cost-effective adaptive capacity-building programs especially at time-strict and resource-limited interventions. The results of such type of quick and cost-effective qualitative investigation of adaptive capacity-building needs could be considered preliminary and a first step for further deeper and extensive quantitative studies, if needed.